Assessment of the knowledge and attitudes of preliminary school students toward smoking in Baghdad (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Early smoking considered as a major challenge for health promoters, as well it is socially not acceptable, thus interventions must tackle childhood starts of smoking.Aim: Assessing the knowledge and attitude of preliminary students towards tobacco use. Methods: A cross-sectional study conducted among 2195, 5th grade students from 30 preliminary schools in Baghdad (15 from each side Karkh & Rusafa) during November 2014. They were selected by multistage sampling technique.Results:  Participated students age ranged between (10-13) years and (51.9%) of them were girls, (54.3%) of their parents were nonsmoker while the rest reported that both or one of them are smokers, direct and indirect risks of cigarette  smoking were known by (82.4%) and (66.2%) respectively, and (70.8%) of students’ families were found to wear their kids from smoking hazards, while more than (50%) of them have received health education massages from their teachers. Sitting near smoker person was not in favor of (86.2%) of the participants, as (51.4%) considered it religiously inconvenient and (34.6%) considered smoking as a sign of no self-confidence. At last, (73.7%) of the surveyed students agreed with smoking prohibition in public places while (25.8%) opposed that.Conclusion: In spite of the high percentage of students’ parents were smokers; nevertheless, risks of smoking are well known by the surveyed students and they showed positive attitudes toward smoking prohibition in public places. Parental advising for quit smoking and urging teachers to educate their students about smoking hazards are thought to be the right action.